2020
DOI: 10.1093/neuonc/noaa222.059
|View full text |Cite
|
Sign up to set email alerts
|

Dipg-08. Electronic Sequencing Provides Optimized Quantification of Serial, Multi-Gene Molecular Response in the CSF of Children With High-Grade Glioma

Abstract: BACKGROUND For pediatric high-grade glioma (pHGG), non-invasive methods for diagnosis and surveillance are needed. Tumors release DNA (tDNA) into cerebrospinal fluid (CSF), allowing for detection of tumor-associated mutations by CSF sampling. We hypothesized that direct, electronic analysis of tDNA with a novel, hand-held platform (Oxford Nanopore MinION) could quantify patient-specific CSF tDNA variant allele fraction (VAF) with improved speed and limit of detection compared to established m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…An attractive alternative to standard sequence-by-synthesis techniques and ddPCR methods for cfDNA profiling is nanopore sequencing. While normally applied as long read technology, Nanopore sequencing can be applied to the short cfDNA fragments rapidly and with lower input, as it depends on the concentration of oligonucleotide ends (84,85). A proof-of-concept study in pHGG showed 85% sensitivity and 100% specificity in CSF samples and demonstrated correlation of VAF detected in cfDNA and radiological response in a clinical trial (85).…”
Section: Future Directions and Alternative Methodologiesmentioning
confidence: 99%
“…An attractive alternative to standard sequence-by-synthesis techniques and ddPCR methods for cfDNA profiling is nanopore sequencing. While normally applied as long read technology, Nanopore sequencing can be applied to the short cfDNA fragments rapidly and with lower input, as it depends on the concentration of oligonucleotide ends (84,85). A proof-of-concept study in pHGG showed 85% sensitivity and 100% specificity in CSF samples and demonstrated correlation of VAF detected in cfDNA and radiological response in a clinical trial (85).…”
Section: Future Directions and Alternative Methodologiesmentioning
confidence: 99%